Avoiding ‘Rona and Passing the Track: When 50 Years of the Canadian Electronic Ensemble Challenges the Limits of Pandemic-Era Live Improvisation - Woloshyn, Alexa (Intersections)

(untitled) (Canadian University Music Society / Société de musique des universités canadiennes, 2021)
For months after instituting COVID-19 pandemic social distancing measures, musicians were required to pivot their creative practices, too often with the dissatisfaction caused by latency and physical separation from collaborators and audiences. This article examines a pandemic-era, socially-distanced project by the Canadian Electronic Ensemble (the CEE) entitled Pass the Track (PtT), which they began in 2020 and released on Bandcamp in 2023. I first position the CEE’s creative practice within live electronic free improvisation (Andean 2022) and categories of liveness (Sanden 2013). I then analyze the process and outcomes of PtT to argue that, despite the lack of spatial and temporal awareness, the project perpetuates the CEE’s value on collaboration and exhibits liveness.